Phylogenetic and sequence analysis of toll like receptor genes (TLR-2 and TLR-4) in buffaloes - Tantia, M S; Mishra, Bina; Banerjee, P; Joshi, J; Upasna, S; Vijh, R K (The Indian Journal of Animal Sciences, 2012)
The toll like receptors play a significant role in innate immune response with TLR2 and TLR4 genes being associated with mastitis in cattle. The sequences of these genes were not known in buffaloes and in the present study we sequenced these 2 genes in buffaloes using 24 samples belonging to 6 diverse buffalo breeds of India. Primers were designed from the cattle data base and the buffalo genomic DNA was amplified. The gene sequences obtained after alignment were submitted to NCBI. The TLR2 gene was 3590 bases with 2 exons and coding for 784 amino acids. The TLR4 gene was 4256 nucleotide bases and consisted of 3 exons and coded for 841 amino acids. Eight SNPs were detected in TLR2 gene out of which 3 were non-synonymous. 25 SNPs were detected in TLR4 gene and out of which 10 were non-synonymous leading to change in amino acids. The 2 genes were found to be highly conserved across all mammalian species, and the phylogenetic relationship revealed the closeness of buffalo species with other ruminants, viz. cattle, sheep and goat compared to mono-gastric animals, viz. pigs and man.